STUDIES ON THE IMMUNOMODULATORY AND THERAPEUTIC EFFICACY OF NEEM (AZADIRACHTA IND/CA) ON ENDOMETRITIS IN REPEAT BREEDING CROSSBRED COWS - KUMAR, AMIT; GUPTA, H P; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
An experiment was designed to investigate the immunomodulatory and therapeutic efficacy of neem on endometritis in repeat breeding crossbred cows. Twenty four cows were selected on the basis of history, breeding records, transrectal examination, white side test and randomly divided into 3 groups (Group A: 30 ml normal saline; Group B: 30 ml hydro-alcoholic neem bark; Group C: 30 ml hydro-acetonic neem bark). Treatments were given intrauterine beginning on the day of estrus for seven days in each group. Cervical mucus samples were collected on the day of estrus before treatment and at subsequent estrus after treatment and tested for appearance, pH, white side test and bacterial load. Blood samples were collected on the day of treatment and 24 hr after treatment and analyzed for glucose, Hb, PCV, TLC and DLC to know health status of the experimental animals. Uterine flushings were collected on the day of estrus before treatment and again on eighth day of first collection i.e. 24 hr after last treatment. These flushings were used for the estimation of total protein, immunoglobulin, TLC and polymorphonuclear cells (PMNs). At subsequent standing estrus following treatment, all cows were artificially inseminated twice using frozen semen 12 hours apart. Pregnancy was confirmed transrectally 45-60 days after insemination. Significant (p<0.05) decline in pH and bacterial load was observed in cervical mucus of the groups after treatment. Hemoglobin, neutrophils, lymphocytes and WBC were increased significantly (p<0.05) in both hydro-alcoholic and hydro-acetonic extract treated groups. Moreover, RBCs and glucose were increased in hydroalcoholic extract treated group. Significant (p<0.05) rise was found in TLC, PMN and immunoglobulin concentration in both the treated groups. Although both the extracts led to improved clinical recovery and conception rates, the hydro-alcoholic extract was more effective. Based on these results, it may be concluded that hydro-alcoholic extract of the neem has a better antibacterial and immuno-modulation and can be used as a therapy for endometritis in repeat breeding crossbred cows.